2010
DOI: 10.1016/j.bbmt.2010.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-Intensity Allogeneic Hematopoietic Stem Cell Transplantation for Relapsed Multiple Myeloma

Abstract: Purpose Despite recent advances, multiple myeloma remains incurable and most patients eventually develop progressive disease. Allogeneic hematopoietic stem cell transplantation (allo HCT) offers a potentially curative option in 10–20% of patients with relapsed or refractory disease. We evaluated the outcome of patients undergoing allo HCT with reduced-intensity conditioning (RIC) for relapsed and/or refractory myeloma at our institution. Methods Fifty-one patients with heavily pretreated, relapsed myeloma, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Rotta et al [21] and a recent study from the M. D. Anderson Center [22] found that high b 2microglobulin levels were an adverse risk factor for overall and progression-free survival; this factor was excluded from analysis in our study due to the relatively high level of non-response to this question. Our study also confirmed previous findings that recipients with an HLA-identical sibling donor had a significant survival advantage over those with other donor types [23,24].…”
Section: Discussionmentioning
confidence: 95%
“…Rotta et al [21] and a recent study from the M. D. Anderson Center [22] found that high b 2microglobulin levels were an adverse risk factor for overall and progression-free survival; this factor was excluded from analysis in our study due to the relatively high level of non-response to this question. Our study also confirmed previous findings that recipients with an HLA-identical sibling donor had a significant survival advantage over those with other donor types [23,24].…”
Section: Discussionmentioning
confidence: 95%
“…The present study does not provide an answer to this question. However, other studies, [19][20][21] including a retrospective EBMT study that is in progress, indicate that allogeneic transplantation might be an option. Still, these studies are not prospective and do not compare results with those of new drug treatment or autologous transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that purine analog containing non-myeloablative chemotherapy enables engraftment of allogeneic hematopoietic progenitor cells (HPC) in patients considered ineligible for myeloablative therapy due to age or medical illness 6–8 . We have previously shown that RIC allo-HCT is associated with durable remission and survival in selected patients with relapsed or refractory MM 9 . In that study of heavily pre-treated patients, progression-free survival (PFS) and OS at 2-years were 19% and 32%, respectively and 24% of patients were still alive after a median follow-up of 27 months.…”
Section: Introductionmentioning
confidence: 98%